Comparison of neutron-physical characteristics of uranium target of assembly "quinta" irradiated by relativistic deuterons and ¹²C nuclei - Artiushenko, M.Yu.; Baldin, A.A.; Berlev, A.I.; Chilap, V.V.; Dalkhajav, O.; Sotnikov, V.V.; Tyutyunnikov, S.I.; Voronko, V.A.; Zhadan, A.A. (Вопросы атомной науки и техники, 2016)
At the present time disposal of spent nuclear fuel and fuel supply problem are two main reasons preventing wide distribution of nuclear power. One of the ways to solve this problem is using Nuclear Relativistic Technologies aimed at forming of maximum hard neutron spectrum in natural or depleted massive uranium targets irradiated by high energy (2…10 GeV) beams of relativistic particles. This paper describes the neutron generation in massive natural uranium target (assembly "QUINTA", mU ~ 500 kg) irradiated by beams of relativistic deuterons and 12C ions with energies of 2 and 4 AGeV at the accelerator Nuclotron (JINR, Dubna). The reactions natU(n,f), ²³⁸U(n,γ), and ⁵⁹Co(n,x) were investigated using activation technique. Comparison of obtained experimental results in dependence on energy of incident beam and type of particles was carried out. Проблема утилизации отработанного ядерного топлива и ограниченность запасов сырья на сегодняшний день являются двумя основными причинами, препятствующими широкомасштабному распространению атомной энергетики. Одним из путей решения данных проблем является использование ядерных релятивистских технологий, которые предлагают использование максимально жѐсткого спектра нейтронов в массивных мишенях из природного или обеднѐнного урана, облучаемых пучками релятивистских частиц высоких энергий (2…10 ГэВ). Данная работа описывает исследование генерации нейтронов в протяжѐнной мишени из природного урана (установка "КВИНТА", mU ~ 500 кг), облучаемой пучками релятивистских дейтронов и ядер ¹²C с энергиями 2 и 4 ГэВ/нукл. на ускорителе «Нуклотрон» (ОИЯИ, Дубна). С помощью активационной методики были исследованы скорости реакций: natU(n,f), ²³⁸U(n,γ), ⁵⁹Co(n,x). Проведено сравнение полученных экспериментальных результатов в зависимости от энергии и вида налетающих частиц. Проблема утилізації відпрацьованого ядерного палива та обмеженість запасів сировини на сьогоднішній день є двома основними причинами, що перешкоджають широкомасштабному поширенню атомної енергетики. Одним із шляхів вирішення даних проблем є використання ядерних релятивістських технологій, які пропонують використання максимально жорсткого спектра нейтронів у масивних мішенях з природного або збідненого урану, що опромінюються пучками релятивістських частинок високих енергій (2…10 ГеВ). Дана робота описує дослідження генерації нейтронів у протяжній мішені з природного урану (установка "КВІНТА", mU ~ 500 кг), яка опромінювалася пучками релятивістських дейтронів та ядер ¹²C з енергіями 2 та 4 ГеВ/нукл. на прискорювачі «Нуклотрон» (ОІЯД, Дубна). За допомогою активаційної методики були досліджені швидкості реакцій: natU(n,f), ²³⁸U(n,γ), ⁵⁹Co(n,x). Проведено порівняння отриманих експериментальних результатів залежно від енергії та виду налітаючих частинок